2014
DOI: 10.1016/j.febslet.2014.05.010
|View full text |Cite|
|
Sign up to set email alerts
|

SPR analysis of promoter binding of Synechocystis PCC6803 transcription factors NtcA and CRP suggests cross‐talk and sheds light on regulation by effector molecules

Abstract: Edited by Miguel De la RosaKeywords: Protein-protein interaction PipX protein 2-Oxoglutarate Cyanobacteria Catabolite gene activator protein Nitrogen metabolism a b s t r a c t Surface plasmon resonance monitoring of the binding of transcription factors cAMP receptor protein (CRP) and nitrogen control factor of cyanobacteria (NtcA) from Synechocystis sp. PCC6803 to promoter fragments of glnA, glnN (NtcA regulon) and cccS (CRP regulon), revealed exclusive CRP binding to cccS, whereas NtcA was bound to all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…Domain interactions in the activated form of NtcA are stabilized by the binding of PipX, which suggests that PipX drives the equilibrium toward the active conformation of NtcA (84,94). In agreement with this, biochemical studies revealed that PipX increases the affinity of NtcA for promoters and the effective affinity of NtcA for 2-OG (88). Modeling of the PipX-NtcA complex on DNA suggests PipX is shown as a surface structure, and 2-OG is shown as blue and red spheres.…”
Section: The Ntca Transcriptional Regulator In Cyanobacteriamentioning
confidence: 62%
See 1 more Smart Citation
“…Domain interactions in the activated form of NtcA are stabilized by the binding of PipX, which suggests that PipX drives the equilibrium toward the active conformation of NtcA (84,94). In agreement with this, biochemical studies revealed that PipX increases the affinity of NtcA for promoters and the effective affinity of NtcA for 2-OG (88). Modeling of the PipX-NtcA complex on DNA suggests PipX is shown as a surface structure, and 2-OG is shown as blue and red spheres.…”
Section: The Ntca Transcriptional Regulator In Cyanobacteriamentioning
confidence: 62%
“…5). This may explain why binding of 2-OG to NtcA results in a relatively small enhancement in the affinity for DNA, compared with a large change in affinity brought about by the binding of cAMP to Crp (85,88). Structural characterization of the 2-OG binding site in NtcA has been valuable for designing chemical derivatives of 2-OG that mimic its signaling function in vivo (89).…”
Section: The Ntca Transcriptional Regulator In Cyanobacteriamentioning
confidence: 99%
“…The subdivision of Cluster I transcripts into two sub-clusters with expression patterns suggestive of PipX and PipY having independent (IA) or additive (IB) effects, respectively, can be rationalized on the bases of the affinity of NtcA for its different binding sites (Espinosa et al, 2007; Forcada-Nadal et al, 2014). NtcA targets from Cluster IB would provide weaker NtcA binding and thus greater dependency on both PipX and PipY.…”
Section: Discussionmentioning
confidence: 99%
“…The PipX protein can form alternative complexes with NtcA and PII and these interactions are, respectively, stimulated and inhibited by 2-OG, providing a mechanistic link between PII signaling and NtcA-regulated gene expression (Espinosa et al, 2006). PipX binds to either, 2-OG-bound NtcA to stimulate DNA binding and transcriptional activity, or to 2-OG-free PII to form PII-PipX complexes (Tanigawa et al, 2002; Vazquez-Bermudez et al, 2002; Llacer et al, 2010; Zhao et al, 2010; Forcada-Nadal et al, 2014), which in turn can bind to the transcriptional regulator PlmA (Labella et al, 2016). While PII is found in all three domains of life as integrator of signals of the nitrogen and carbon balance, PipX, NtcA, and PlmA are all restricted to cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…PCC 7120 (hereafter S. elongatus and Anabaena , respectively) showed that activation of NtcA-dependent genes is enhanced by PipX binding to NtcA (Espinosa et al, 2006, 2007; Valladares et al, 2011; Forcada-Nadal et al, 2014). Under nitrogen limitation, 2-OG stimulates NtcA binding to target sites (Vázquez-Bermúdez et al, 2002), activating transcription (Tanigawa et al, 2002) and favoring complex formation between NtcA and PipX (Espinosa et al, 2006) (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%